A Simple Proof of the Brouwer Fixed Point Theorem: S. Dhompongsa, J. Nantadilok - Team, Support (Thai Journal of Mathematics, 2015)
We give a new proof of the Brouwer fixed point theorem which is more elementary than all known ones. The only tool we use is the Tietze (continuous) extension theorem. The idea of the proof suggests some successful computation of a fixed point.